Recycling Mimeograph-Printed Newsprint Paper - E. L Mari; A.S Torres; C.O Austria (Universitas Gadjah Mada, 2011)
Virgin newsprint paper from thermo-mechanical pulp was subjected to a laboratory recycling scheme, which involved mimeograph-printing, re-pulping, de-inking, washing, refining, and handsheetforming, without adding other fibre in between cycles. Fibre dimension, pulp freeness and paper properties were determined after each cycle until the fifth, at which about 20% of the original material remained. The remaining fibre was then mixed with virgin pulp, the original newsprint and unsorted mixed office waste to determine the proportion necessary for acceptable properties. The results indicated remarkable modification in distribution of fibre properties, a decreasing amount of long fibre with corresponding increase of short fibre in the course of recycling and loss of fibre. Refining generally improved the strength properties of paper from recycled fibre. About 20 % to 30 % of either thermo-mechanical pulp or unsorted mixed office waste was found sufficient for blending with recycled fibre to obtain acceptable strength properties.